Vähetuntud fakte Eesti luterlike koguduste ajaloost nõukogude Venemaal - Shkarovskij, Mihhail (Usuteaduslik Ajakiri, 2002)
Mikhail Shkarovskij, Hidden Facts of the History of Estonian Lutheran Parishes in Soviet Russia in 1917-1945. The first years following the Bolshevist Revolution witnessed a marked growth in the religious and national self-concept and consequently in the congregational life of Estonian Lutherans. This resulted for the first time in Russian history in the establishment of the Estonian Higher Church Council (HCC) in 1921. The Council was led by bishops until 1929 - first Oskar Paisa, later Aleksander Jürgenson. The number of churches grew, reaching 18 by the mid-1920’s in the Northwestern region alone. Although the antichurch actions by the Soviet authorities had been exerting a harmful influence on religious life ever since 1918, they were confined to certain locations until the late 192O’s, without having any profound influence on the life of the churches. Since 1929, the situation changed significantly. The systematic persecution policy by the Soviet authorities led to the closure of all Estonian churches within 10 years, as well as to the liquidation of the congregations and the imprisonment of all the pastors and many lay activists. In 1929-1937, the HCC continued its formal existence but did not play a meaningful role - the congresses of Estonian church representatives ceased to be held, etc. The third period lasted from 1938 to 1945. The destruction process was completed by the partial deportation of the Estonians from frontier zones. During the years of the Nazi German occupation some churches were re-established briefly in some parts of the Leningrad district but were closed again in 1944-1945.